2019
DOI: 10.1097/gme.0000000000001366
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse and vasomotor symptoms among midlife women

Abstract: Objective: Childhood maltreatment is related to adverse health outcomes. However, the relation of childhood maltreatment to the menopause transition—a universal transition for women often accompanied by troubling symptoms such as vasomotor symptoms—is relatively underexplored. This study tested whether childhood abuse and neglect are associated with menopausal vasomotor symptoms, utilizing both physiologic and prospective self-report measures of vasomotor symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…There are studies which show that adverse childhood experiences associate with a myriad of adverse health outcomes, including vasomotor symptoms. Childhood abuse is associated with increased vasomotor symptom reporting in adulthood [20,21]. The sense of coherence may not have had the opportunity to develop robustly for women born in the years 1944-1948, since that generation lived in the aftermath of a great war, in contrast to women born ten years later, from 1954 to 1958.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies which show that adverse childhood experiences associate with a myriad of adverse health outcomes, including vasomotor symptoms. Childhood abuse is associated with increased vasomotor symptom reporting in adulthood [20,21]. The sense of coherence may not have had the opportunity to develop robustly for women born in the years 1944-1948, since that generation lived in the aftermath of a great war, in contrast to women born ten years later, from 1954 to 1958.…”
Section: Discussionmentioning
confidence: 99%
“…The limited research available suggests that childhood abuse may correlate with symptom severity. Carson et al reported that women with a history of physical or sexual abuse have a 1.5–2 times greater risk of vasomotor sleep symptoms than those without this history [12]. This association, however, was not noted in women who reported only emotional abuse.…”
mentioning
confidence: 99%
“…The literature search strategy identified 194 articles, of which 117 were excluded at various stages of the search, eventually producing a final selection of 19 articles (Fig. 1), five of which were related to menopausal symptoms [10][11][12][13][14], two related to genitourinary symptoms [15,16], five studies on psychological health or physical conditions [17][18][19][20][21] three on sexual health [22][23][24], and four on cardiovascular or metabolic problems [25][26][27][28]. Nine studies were crosssectional studies [12-17, 19, 22, 23] and ten were cohort studies [10,11,18,20,21,[24][25][26][27][28]; two Brazilian [11,22], two Australian [17,24] and the rest from USA.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 (Ref. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]) displays a summary of the main characteristics of the selected studies (study design, population, intervention, objective, and main results). The participants' mean age or age range was reported in all articles, but not the time since the violence episode, which was described in only one study [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation